Comparative analysis of HHV and LHV values of biocoke fuel from palm oil mill solid waste - Gani, Asri; Erdiwansyah, E.; Desvita, Hera; Munawar, Edi; Rizalman, Mamat; Nizar, Muhammad Afdi; Darnas, Yeggi; Sardjono, Ratnaningsih Eko (Elsevier Ltd, 2024)
This research aims to investigate and compare the energy value of different biocoke and raw palm oil-biomass. Applying pressure and heating simultaneously during biocoke production is a direct method used in this research. The results of the proximate analysis showed that the water content in each sample tested was below 10%. The water content can be reduced to 5% for all samples except oil palm-midrib. The highest raw biomass heating value was recorded from palm-kernel-shell at 16.83 MJ/kg; the lowest oil palm-midrib was 14.60%. Meanwhile, the highest lower heating value was recorded from biocoke at 19.08 MJ/kg, and the weakest empty-fruit-bunches 17.01 MJ/kg.